Implications of bank regulation for loan supply and bank stability: A dynamic perspective - Monika Bucher; Diemo Dietrich; Achim Hauck (Deutsche Bundesbank, 2018)
A bank's decision on loan supply and capital structure determines its immediate bankruptcy risk as well as the future availability of internal funds. These internal funds in turn determine a bank's future costs of external finance and future vulnerability to bankruptcy risks. We study these intra- and intertemporal links and analyze the influence of risk-weighted capital-to-asset ratios, liquidity coverage ratios and regulatory margin calls on the dynamics of loan supply and bank stability. Only regulatory margin calls or large liquidity coverage ratios achieve bank stability for all risk levels, but for large risks a bank will stop credit intermediation.
Keywords: G01; G21; G28; E32; 330; bank lending; banking crisis; bank capital regulation; liquidity regulation